Accelerated diagnostic protocol using high-sensitivity cardiac troponin T in acute chest pain patients. (1st April 2015) - Meller, Bernadette; Cullen, Louise; Parsonage, William A.; Greenslade, Jaimi H.; Aldous, Sally; Reichlin, Tobias; Wildi, Karin; Twerenbold, Raphael; Jaeger, Cedric; Hillinger, Petra; Haaf, Philip; Puelacher, Christian; et al.
Abstract: Background: We aimed to evaluate the efficacy and safety of using high-sensitivity cardiac troponin T (hs-cTnT) within an accelerated diagnostic protocol (ADP) in patients presenting with symptoms suggestive of acute myocardial infarction (AMI) for rapid rule-out of AMI. Methods: In two independent large multicenter studies, levels of hs-cTnT at presentation and at 2 h were combined with the Thrombolysis In Myocardial Infarction (TIMI) risk score and ECG findings. The ADP defined patients with normal levels of hs-cTnT at presentation and 2 h, a TIMI score ≤ 1, and normal ECG findings as candidates for rapid rule-out of AMI and rapid discharge. Major adverse cardiac events (MACEs) occurring within 30-days were centrally adjudicated by two independent cardiologists. Results: In the derivation cohort, among 1085 consecutive patients 198 patients (18.2%) had a MACE. The ADP classified 374 patients (34.5%) as low-risk. None of these patients had a MACE at 30 days, resulting in a negative predictive value (NPV) of 100% (95% CI, 99.0–100%) and a sensitivity of 100% (95% CI, 98.2%–100%). In the validation cohort, among 1590 consecutive patients 231 patients (14.5%) had a MACE. The ADP classified 641 patients (40.3%) as low-risk. 6 of these patients had a MACE at 30 days, resulting in a NPV of 99.1% (95% CI, 98.0–99.6%) and a sensitivity of 97.4% (95% CI, 94.5–98.8%). Conclusions: The ADP including hs-cTnT allows early identification 35 to 40% of patients to be at extremely low risk of MACE and therefore ideal candidates for outpatient management.